Absolute configuration of spiro-flavostilbenoids from Yucca schidigera Roezl ex Ortgies: First indication of (2R)-naringenin as the key building block. (March 2023) - Pecio, Łukasz; Alilou, Mostafa; Kozachok, Solomiia; Orhan, Ilkay Erdogan; Eren, Gökçen; Şenol Deniz, Fatma Sezer; Stuppner, Hermann; Oleszek, Wiesław
Abstract: The absolute configurations of the known but unusual spiro-flavostilbenoids found in the bark of Yucca schidigera Roezl ex Ortgies, were determined by applying time-dependent density functional theory simulation of electronic circular dichroism spectra. The absolute configurations obtained were as follows: (2 S, 3 R ) for yuccaol A, yuccaol D and yuccalide A; (2 S, 3 S ) for yuccaol B, yuccaol C and yuccaol E; (2 S, 3 S, 2′ S, 3′ S ) for gloriosaol A; (2 S, 3 R, 2′ S, 3′ R ) for gloriosaol C; (2 S, 3 S, 2′ S, 3′ R ) for gloriosaol D; (2 S, 3 R, 2′ S, 3′ S ) for gloriosaol E. These findings indicate that the compounds are all biosynthetic derivatives either of (2 R )-naringenin and trans -resveratrol or of trans -3, 3 ′, 5, 5 ′ -tetrahydroxy-4′-methoxystilbene. In contrast, gloriosaols are direct derivatives of yuccaols (note that substituting by stilbenoid changes the absolute configuration of C-2 naringenin carbon to 2 S ). A putative mechanism for their biosynthesis is proposed taking into account key aspects of regio- and stereoselectivity. Yuccaol B and gloriosaol A showed in vitro moderate inhibitory effects against acetyl-/butyrylcholinesterases (AChE/BChE) with IC50 values of 43/81 and 45/65 μM respectively. The selectivity index values calculated from the IC50 values of BChE and AChE were 1.9 and 1.4. Molecular docking simulations showed their interaction with the peripheral anionic site of human AChE and the catalytic site of the human BChE. Graphical abstract: Image 1 Highlights: The absolute configurations of spiro-flavostilbenoids from Y. schidigera were elucidated. Their biosynthetic origin from unusual (2 R )-naringenin was proposed. Yuccaol B and gloriosaol A showed moderate in vitro AChE/BChE inhibitory activities. Molecular docking of yuccaol B and gloriosaol A to hAChE/hBChE was performed.